Angiographic evidence of proliferative retinopathy predicts neuropsychiatric morbidity in diabetic patients. (May 2016) - Serlin, Yonatan; Shafat, Tali; Levy, Jaime; Winter, Aaron; Shneck, Marina; Knyazer, Boris; Parmet, Yisrael; Shalev, Hadar; Ur, Ehud; Friedman, Alon
Highlights: We hypothesized that severe diabetic retinopathy mirrors BBB damage and predicts neuropathology. We conducted a retrospective study among subjects with DM and angiography-proven retinopathy. Patients with severe retinopathy had significantly higher rates of all-cause and specific brain pathologies. Proliferative retinopathy was an independent predictor for all-cause brain impairments, epilepsy and mortality. Abstract: Introduction: Diabetic retinopathy (DR) is a common vasculopathy categorized as either non-proliferative (NPDR) or proliferative (PDR), characterized by dysfunctional blood-retinal barrier (BRB) and diagnosed using fluorescein angiography (FA). Since the BRB is similar in structure and function to the blood-brain barrier (BBB) and BBB dysfunction plays a key role in the pathogenesis of brain disorders, we hypothesized that PDR, the severe form of DR, is likely to mirror BBB damage and to predict a worse neuropsychiatric outcome. Methods: A retrospective cohort study was conducted among subjects with diabetes ( N = 2982) with FA-confirmed NPDR ( N = 2606) or PDR ( N = 376). Incidence and probability to develop brain pathologies and mortality were investigated in a 10-year follow-up study. We used Kaplan–Meier, Cox and logistic regression analyses to examine association between DR severity and neuropsychiatric morbidity adjusting for confounders. Results: Patients with PDR had significantly higher rates of all-cause brain pathologies ( P < 0.001), specifically stroke ( P = 0.005), epilepsy ( P = 0.006) and psychosis ( P = 0.024), and a shorter time to develop any neuropsychiatric event ( P < 0.001) or death ( P = 0.014) compared to NPDR. Cox adjusted hazard ratio for developing all-cause brain impairments was higher for PDR (HR = 1.37, 95% CI 1.16–1.61, P < 0.001) which was an independent predictor for all-cause brain impairments (OR 1.30, 95% CI 1.04–1.64, P = 0.022), epilepsy (OR 2.16, 95% CI 1.05–4.41, P = 0.035) and mortality (HR = 1.35, 95% CI 1.06–1.70, P = 0.014). Conclusions: This is the first study to confirm that angiography-proven microvasculopathy identifies patients at high risk for neuropsychiatric morbidity and mortality.